Synthesis of Nano‐Hierarchical Ferrierite with Sole Template and Its Catalytic Application in n‐Butene Skeletal Isomerization. Issue 34 (9th September 2019) - Liu, Wen; Hu, Haiqiang; Ke, Ming; Liu, Yang; Zhang, Lei; Xia, Chengjie; Wang, Qi
Abstract: Nano‐hierarchical ferrierite( FER ) was successfully synthesized by using pyrrolidine as sole organic structure directing( OSDA ) agent under static hydrothermal conditions.SEM images showed that the morphology of the product was a loose three‐stage accumulation structure by nano‐rod crystal grains .The influence of crystallization temperature, gel alkalinity, crystallization time and the amount of OSDA on synthesis of FER was investigated in detail.Moreover, FER catalytic performance in n‐butene skeletal isomerizatio was investigated.The results showed that, compared with the commercial FER, the nano‐hierarchical FER showed better catalytic activity. Abstract : Nano‐hierarchical ferrierite( FER ) was successfully synthesized by using pyrrolidine as sole organic structure directing( OSDA ) agent under static hydrothermal conditions, which(S2) shown better catalytic performance than commercial ferrierite(SC) in n ‐butene skeletal isomerization.